2010
DOI: 10.1021/jp108865q
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Effects on DNA Translocation in a Nanochannel Coated with a Self-Assembled Monolayer

Abstract: A biomimetic nanochannel coated with a self-assembled monolayer (SAM) can be used for sensing and analyzing biomolecules. The interaction between a transported biomolecule and a SAM governs the mechanically or electrically driven motion of the molecule. To investigate the translocation dynamics of a biomolecule, we performed all-atom molecular dynamics simulations on a single-stranded DNA in a solid-state nanochannel coated with a SAM that consists of octane or octanol polymers. Simulation results demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Interestingly, in the nanochannels seeded with 0.5× TBE, we observed intermittent (stick-slip) motion of the DNA molecules through the nanochannel similar to previous reports 32, 84 at measurements performed <150 V/cm (Figure 6c). Based on MD simulations 96 and theoretical computations, 97 a highly negatively charged DNA molecule translocating through a nanochannel interacts both electrically (attractive or repulsive forces) and hydrodynamically with the channel wall. Therefore, we attributed the intermittent motion of DNA to latent electrical interactions between the charged DNA molecule and the thick EDL and this presents the possibility that at this field strength, the driving force was less than the interfacial force.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in the nanochannels seeded with 0.5× TBE, we observed intermittent (stick-slip) motion of the DNA molecules through the nanochannel similar to previous reports 32, 84 at measurements performed <150 V/cm (Figure 6c). Based on MD simulations 96 and theoretical computations, 97 a highly negatively charged DNA molecule translocating through a nanochannel interacts both electrically (attractive or repulsive forces) and hydrodynamically with the channel wall. Therefore, we attributed the intermittent motion of DNA to latent electrical interactions between the charged DNA molecule and the thick EDL and this presents the possibility that at this field strength, the driving force was less than the interfacial force.…”
Section: Resultsmentioning
confidence: 99%
“…This effect was previously observed for DNA translocation studies in nanocolumns 34,45,46 and arose from adsorption/desorption behavior of the solute with the channel walls. 4749 In addition, this stick/slip motion can arise from dielectrophoretic trapping as well, which results from column wall surface roughness producing inhomogeneity in the electric field. 34 …”
Section: Resultsmentioning
confidence: 99%
“…It was experimentally and theoretically shown that such interaction can affect the polymer translocation [39, 40, 41]. Such interaction was also investigated using molecular dynamics simulations [42]. Simulation results showed that it is possible, by chemically modifying the pore surface [43], to reduce such interaction and confine DNA near the pore center [42].…”
Section: Discussionmentioning
confidence: 99%